The Effect of Ellagic Acid on Hepatic Lipid Metabolism and Antioxidant Activity in Mice - Xu, Qiuying; Li, Shuwei; Tang, Wenjie; Yan, Jiayou; Wei, Xiaolan; Zhou, Mengjia; Diao, Hui (Frontiers in Physiology, 2021)
Accumulating evidence has demonstrated that the imbalance of lipid metabolism and antioxidant capacity leads to damage to liver. The present study aimed to investigate the effects of Ellagic acid (EA), a phenolic compound, on hepatic lipid metabolism and antioxidant activity in mice. In our study, thirty-six C57BL/6J mice were divided into three groups: (1) control (CON); (2) basal diet+0.1% EA (EA1); (3) basal diet+0.3% EA (EA2). After the 14-day experiment, the liver was sampled for analysis. The results showed that 0.3% EA administration increased the liver weight. Total cholesterol (T-CHO) and Low-density lipoprotein cholesterol (LDL-C) activities decreased and High-density lipoprotein cholesterol (HDL-C) activity increased by EA supplementation. Meanwhile, dietary supplementation with EA dose-dependently decreased the acetyl-CoA carboxylase (ACC) protein abundance and increased the phospho-hormone-sensitive lipase (p-HSL), carnitine palmitoyltransferase 1B (CPT1B) and peroxisome proliferator-activated receptor alpha (PPARα) protein abundances. Moreover, EA supplementation reduced the malonaldehyde (MDA) concentration and increased the superoxide dismutase (SOD) and catalase (CAT) concentrations. The protein abundances of phospho-nuclear factor-E2-related factor 2 (p-Nrf2), heme oxygenase-1 (HO-1) and NAD(P)H: quinone oxidoreductase 1 (NQO1) increased by EA supplementation in a dose-dependent manner. Taken together, EA supplementation promoted the lipid metabolism and antioxidant capacity to maintain the liver health in mice.